Architectural development of historic health care institutions in Vilnius city - Stauskis, Gintaras (Journal of Architecture and Urbanism, 2010)
For centuries health institutions have been the most traditional communityoriented providers of public services. The paper focuses on the initial steps of urban development of health facilities in Vilnius city. historic health institutions are analysed as a specific prototype of what is understood today as a “hospital”. In the paper special attention is drawn to the process of emerging of “a hospital” as an independent public institution, its connections to other public buildings, its urban integrity with adjusting and surrounding development as well as its architectural importance for Vilnius city. having emerged as a consistent part of religious and sacral complexes, health institutions (špitolės – in Lithuanian) occupied a part of space in traditional convents, located throughout Vilnius old Town. In early years (around the 15th–16th c) health and treatment spaces were based in ordinary rooms of convents and monasteries. Later in the 17th–18th c they were transferred to specially designated blocks and houses within a convent territory and occupied a major part of spaces there. In the late 18th – 18th c health facilities gradually were disconnected from convents and churches to separate building complexes and finally became completely a new and independent type of public institutions. during the historical periods of development health complexes changed their functional layout and so their planning from initial missions of “separation” and “isolation” to “care” and developed finally to “healing” and “cure”. Analysis of selected cases in Vilnius old Town reveals that as long as changes in urban location of health complexes took place, it was followed by their functional evolution. Making an integral part in numerous sacral complexes, usually consisting of a church, convent, healing centre, garden and cemetery, health institutions were a part of important “architectural hills” that are clearly notable as vertical and spatial landmarks in the surrounding townscape of Vilnius city. Artistic spatial arrangement and architectural expression are the other specific traits that distinguish health complexes – hospitals – in the context of surrounding development. health complexes have always played the most important public role in Vilnius city as centres of social aid, community life, religion, culture and health services for local neighbourhoods. Research on the development of health institutions in historical run is a strong foundation to build up the perspectives for architectural and municipal policies for the future of these complexes. The issue gains special importance in the recent situation of essential transformation of the public health care system in Lithuania and in Vilnius city. Istorinių sveikatos priežiūros objektų architektūrinė raida Vilniaus mieste Santrauka. Straipsnyje pateikiama sveikatos priežiūros įstaigų – šiandienos ligoninių prototipo – urbanistinės raidos analizė istoriniu rakursu. Atskleidžiama pirmųjų sveikatos priežiūros objektų – gydyklų – raidos chronologija išryškina jų ryšius su kitais visuomeniniais kompleksais, jungtis su gretimu ir aplinkiniu miesto apstatymu, taip pat architektūrinę svarbą Vilniaus miestui. Atsiradę po Vilniaus senamiestį pasklidusiuose vienuolynų pastatuose nuo XV a., sveikatos priežiūros objektai pradžioje užėmė dalį jų gyvenamųjų patalpų. Vėliau XVI-XVII a. gydymo paslaugos buvo tolydžio perkeliamos į atskirus vienuolynų pastatus ar jų priskirtas dalis, kur užėmė didžiąją dalį patalpų. XVIII–XIX a. sveikatos priežiūros pastatai palaipsniui prarado glaudų rysį su sakraliniais pastatais, atsiskyrė nuo jų ir tapo nauju viešųjų paslaugų pastato – ligoninės – tipu. Per raidos šimtmečius sveikatos priežiūros ir gydymo pastatai įgavo savo unikalią funkcinę ir erdvinę struktūrą pagal teikiamas paslaugas, kurias pradžioje sudarė atskyrimas, globa bei priežiūra, vėliau – gydymas ir sveikatos priežiūra. Atliktas tyrimas rodo, kad sveikatos priežiūros gydymo pastatams atsiskiriant nuo vienuolynų, keitėsi ir jų funkcinė struktūra. Būdami dalimi sakralinių kompleksų, kuriuos dažniausiai sudarė bažnyčia, vienuolynas, gydykla, sodas ar parkas bei kapinės, gydymui naudojami vienuolynų pastatai išsiskyrė Vilniaus siluetuose ir panoramose – jie buvo raiškių „architektūrinių kalvų“ dalimi. Šių pastatų grupių išraišką lėmė jų ypatinga erdvinė kompozicija bei architektūrinė raiška. Sveikatos priežiūros ir gydymo pastatai per visus laikus išlaikė itin glaudžius ryšius su vietos bendruomenėmis, teikdami joms socialinę pagalbą ir sveikatos priežiūrą, būdami religijos ir kultūros centrai. Šių pastatų kompleksų istorinės raidos tyrimas yra tvirtas pagrindas, skirtas paremti šių kompleksų architektūrinės tvarkybos ir municipalinės politikos principams. Šis klausimas yra ypač aktualus šiandieną, kai pradedama radikaliai pertvarkyti sveikatos priežiūros sistemą Lietuvoje ir Vilniaus mieste. Reikšminiai žodžiai: urbanistinis planavimas, sveikatos priežiūros įstaigų architektūra, socialinė pagalba, siluetas, kraštovaizdis, funkcinė struktūra, kompozicija, ligoninė. First Published Online: 22 May 2013